2002
DOI: 10.1053/ejvs.2002.1693
|View full text |Cite
|
Sign up to set email alerts
|

Does the Angiotensin-Converting Enzyme (ACE) Gene Polymorphism Affect Rate of Abdominal Aortic Aneurysm Expansion?

Abstract: the wide inter-individual variability in AAA expansion rate is likely to reflect complex genetic and environmental interactions, but the lack of any relationship with ACE genotype suggests that differences in vascular ACE activity in aortic tissue are not major determinants of the variability in rate of AAA dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…The presence of the insertion leads to decreased ACE activity in plasma. ACE I/D genotype failed to associate with the incidence and rate of AAA expansion in Japanese and British studies, respectively [36,37]. When the subject pool was restricted to normotensive individuals, the DD genotype was found to be more common in AAA patients compared with controls [38].…”
Section: Evidence Linking Angiotensin Peptides To Human Abdominal Aormentioning
confidence: 91%
“…The presence of the insertion leads to decreased ACE activity in plasma. ACE I/D genotype failed to associate with the incidence and rate of AAA expansion in Japanese and British studies, respectively [36,37]. When the subject pool was restricted to normotensive individuals, the DD genotype was found to be more common in AAA patients compared with controls [38].…”
Section: Evidence Linking Angiotensin Peptides To Human Abdominal Aormentioning
confidence: 91%
“…Because the D allele of the ACE gene is associated with increased serum levels of circulating ACE, investigators suggested that ACE gene polymorphism may be useful as a marker or predictor of human AAA formation [40]. However, another study failed to find any relationship between ACE I/D polymorphism and AAAs [41]. The controversy between these two ACE polymorphism studies may be partially attributable to different populations and a small number of patients.…”
Section: Ras and Human Aaasmentioning
confidence: 99%
“…Two studies have found that ACE polymorphisms resulting in elevated levels of ACE are associated with a predisposition for developing AAAs in normotensive [177] and hypertensive patients [86]. However, Hamano et al found no differences in the distribution of ACE genotypes in patients affected by AAA [178] and Yeung et al found no difference in ACE polymorphism and AAA expansion rate [179]. When comparing genetic studies of this nature, it must be remembered that the conflicting results may be due to variance of polymorphism, and it's subsequent impact, in populations with differing genetic backgrounds…”
Section: Consequences Of Ace Polymorphismmentioning
confidence: 99%